The readiness of Lesotho high schools' management teams to implement The Curriculum and Assessment Policy of 2009 - Mutebi, Richard (University of the Free State, 2019)
The dynamism of the contemporary life poses a constant need for many countries to adopt new education systems that empower their citizens to keep pace with the rest of the globe in various areas. To achieve this objective, many scholars, and researchers recognise the need for effective management in the education systems to support adaptation of the new educational systems. Extreme poverty and high rate of unemployment, high rates of HIV and AIDS prevalence, as well as lack of proper skills in technical and managerial areas are among the most challenging issues affecting Lesotho. As such, to respond to these challenges, Lesotho enacted CAP 2009 to guide the introduction and implementation of the new curriculum seen as the vehicle through which the country would respond to its challenges. Therefore, for its effective implementation, the School managers must be ready to support its implementation. Guided by Critical Rationalism, this study focused on the readiness of the school management teams to implement CAP 2009 in Lesotho schools .Two constructs of Rogan and Grayson (2003) theory of curriculum implementation were used. Rogan and Grayson (2003) propose that when the three constructs are well managed (although two are used in study), they can culminate in the effective implementation of a new curriculum in schools. Besides the theory, I used literature study, policy analysis and a survey, in an empirical study reinforced by mixed methodology strategy. Therefore, within the context of this study, the levels of operation of Rogan and Grayson theory of curriculum implementation constructs namely, Profile of Implementation and Capacity to support Innovation; and their sub constructs acted as standard pointers during the survey. These constructs helped to reveal the realities of the implementation of CAP 2009 and the subsequent IC approach in Lesotho schools during the survey. The survey revealed that the school management teams were moderately ready on the construct of profile of implementation, which encompasses the nature of classroom interaction, integrated curriculum and assessment. However, on the construct Capacity to support Innovation the survey revealed uncertainty coupled with some challenges manifested by the silences revealed in the policy analysis that may pose a threat to the school management teams within their schools during the implementation of CAP 2009. These challenges include lack of resources, and inadequate training for the managers for them to play their roles effectively. The roles, which involve planning, leading, control and expertise.
Dissertation (M.Ed. (Policy Studies))--University of the Free State, 2019
Keywords: School management team; Integrated curriculum; Policy implementation; Curriculum implementation; Lesotho education